2015
DOI: 10.1249/mss.0000000000000536
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance and Commitment Therapy Improves Exercise Tolerance in Sedentary Women

Abstract: An acute ACT intervention increased high-intensity ETT and postexercise enjoyment and reduced perceived effort in low-active women. Further investigations of ACT as an effective intervention for enhancing the established health benefits of high-intensity exercise need to be provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
42
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 43 publications
5
42
0
Order By: Relevance
“…Furthermore, our team (Ivanova et al 2015) demonstrated that ACT increased exercise enjoyment following a session of high-intensity cycle ergometer exercise. Specifically, Ivanova et al (2015) provided empirical evidence for the efficacy of ACT in reducing perceived effort, increasing exercise enjoyment, and improving exercise tolerance for low-active women randomized to the ACT group, as compared to the implementation intentions group.…”
mentioning
confidence: 91%
See 4 more Smart Citations
“…Furthermore, our team (Ivanova et al 2015) demonstrated that ACT increased exercise enjoyment following a session of high-intensity cycle ergometer exercise. Specifically, Ivanova et al (2015) provided empirical evidence for the efficacy of ACT in reducing perceived effort, increasing exercise enjoyment, and improving exercise tolerance for low-active women randomized to the ACT group, as compared to the implementation intentions group.…”
mentioning
confidence: 91%
“…Provided that implementation intentions address only one factor (i.e., planning) of physical activity adoption and maintenance, other barriers to exercise-related maintenance may be better addressed by alternative interventions. Particularly, acceptance and commitment therapy (ACT), a form of cognitivebehavioral psychotherapy (Hayes et al 1999), is receiving increasing support in the literature as an effective intervention for improving acute exercise tolerance (Ivanova et al 2015), as well as short-term (i.e., 5-weeks) physical activity adherence (e.g., Butryn et al 2011). A core assumption of ACT is that negative and unpleasant feelings and experiences are neither good nor bad, but rather a facet of human life (Hayes et al 1999).…”
mentioning
confidence: 99%
See 3 more Smart Citations